Photo-induced actuator using temperature and light dual responsive azobenzene containing ion gel in ionic liquid. (15th January 2020) - Ma, Xiaofeng; Lan, Xiaoyu; Wu, Linlin; Wang, Lei; Gu, Qun; Shi, Yijun; Gu, Xiaoli; Luo, Zhenyang
Graphical abstract: Highlights: We prepared azobenzene containing random copolymers (P(AzoMA- r -BA)) and ion gel (BA-AzoMA ion gel). LCST of P(AzoMA- r -BA) depends on photo-isomerization states of azobenzene. Photo-induced LCST transition of P(AzoMA- r -BA) was reversible at certain temperatures. BA-AzoMA ion gel shows reversible thermo- and photo-induced volume changing. Photo-induced actuator with reversible bending behavior can be realized. Abstract: A series of well-defined random copolymers comprising butyl acrylate (BA) and 4-phenylazophenylmethacrylate (AzoMA) (P(AzoMA- r -BA)) are prepared successfully by reversible addition fragmentation chain transfer (RAFT) polymerization. P(AzoMA- r -BA)s show LCST-type phase transition in 1-butyl-3-methylimidazolium bis(trifluoromethanesulfone)amide ([C4 mim][NTf2 ]). LCST depends on the photoisomerization state of azobenzene, as well as on the AzoMA composition in the random copolymers. LCST of (P( cis -AzoMA- r -BA) is significantly higher than that of P( trans -AzoMA- r -BA), because cis -AzoMA and trans -AzoMA behave as solvato-philic and solvato-phobic comonomer, respectively. At a bistable temperature, photo-induced phase separation is completely reversible. Secondly, based on this phenomenon, a thermo-/photo- responsive ion gel (BA-AzoMA ion gel) can be prepared by free radical polymerization of BA and AzoMA using ethylene glycol dimethacrylate (EGDMA) as crosslinker in [C4 mim][NTf2 ]. BA-AzoMA ion gel shows high temperature contraction and low temperature expansion behavior, due to LCST-type phase behavior of polymer system consisting of AzoMA and BA. Contraction temperature of BA-AzoMA ion gel depends on photoisomerization state of the azobenzene group in polymers. At a bistable temperature, photo-induced expansion-contraction is reversible. Finally, a Photo-induced actuator can be realized using BA-AzoMA ion gel at suitable temperatures, featuring reversible bending by alternate irradiating with visible and UV light. The bending behavior is also demonstrated.